The perishable forms of soil: The agrarian ruin as a philosophical inflection of the landscape: pictorial sequence - Luque Cuesta, Fernando; Hidalgo Rodríguez, María Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article studies the ruined agrarian architectural heritage of Andalusia, the causes of its deterioration, such as agricultural industrialization, and some of its consequences, such as the rural exodus. Part of the results are shown in an audiovisual piece assembled from eight paintings that illustrate the degeneration of the landscape and rural buildings, until these are defined as ruins and integrated into the ground. As conclusions, the need to change the production models and preserve the agrarian ruins as part of the culture is evident.